Islam dan ilmu pengetahuan: jejak kontribusi dalam membangun peradaban dunia dari masa ke masa - octaria, sayyidah belqis (Maliki Interdisciplinary Journal, 2026)
This article explores the significant contributions of Islam to the development of science and knowledge, from the golden age of Islamic civilization to the modern era. From the outset, Islam has encouraged its followers to seek knowledge as a form of worship, as reflected in many verses of the Qur’an and hadiths. This religious emphasis gave rise to prominent Muslim scholars such as Al-Khwarizmi in mathematics, Ibn Sina in medicine, and Al-Farabi in philosophy, whose works laid the foundation for modern scientific disciplines. This study employs a qualitative approach using a library research method, analyzing various scholarly sources related to Islamic intellectual history, Islamic epistemology, and the integration of religious and scientific knowledge. Through translation efforts and intellectual development, Islamic civilization served as a crucial bridge in transmitting knowledge from the East to the West, significantly influencing the European Renaissance. In the contemporary era, the integration of religious and secular sciences is being revitalized, particularly in Islamic educational institutions such as UIN Maulana Malik Ibrahim Malang. This integration model aims to eliminate the dichotomy between religious and worldly knowledge by combining both within the educational curriculum. Such an approach demonstrates that Islamic values remain relevant in addressing modern challenges and can foster a generation that excels in science while upholding strong moral values. Therefore, Islam is not only a part of the historical development of science but also holds great potential in shaping the future of a more holistic and ethical scientific civilization.